Food Xanthan Polysaccharide Sulfation Process with Sulfamic Acid - Aleksandr S. Kazachenko (MDPI AG, 2021)
Xanthan is an important polysaccharide with many beneficial properties. Sulfated xanthan derivatives have anticoagulant and antithrombotic activity. This work proposes a new method for the synthesis of xanthan sulfates using sulfamic acid. Various N-substituted ureas have been investigated as process activators. It was found that urea has the greatest activating ability. BBD of xanthan sulfation process with sulfamic acid in 1,4-dioxane has been carried out. It was shown that the optimal conditions for the sulfation of xanthan (13.1 wt% sulfur content) are: the amount of sulfating complex per 1 g of xanthan is 3.5 mmol, temperature 90 °C, duration 2.3 h. Sulfated xanthan with the maximum sulfur content was analyzed by physicochemical methods. Thus, in the FTIR spectrum of xanthan sulfate, in comparison with the initial xanthanum, absorption bands appear at 1247 cm−1, which corresponds to the vibrations of the sulfate group. It was shown by GPC chromatography that the starting xanthan gum has a bimodal molecular weight distribution of particles, including a high molecular weight fraction with Mw > 1000 kDa and an LMW fraction with Mw < 600 kDa. It was found that the Mw of sulfated xanthan gum has a lower value (~612 kDa) in comparison with the original xanthan gum, and a narrower molecular weight distribution and is characterized by lower PD values. It was shown by thermal analysis that the main decomposition of xanthan sulfate, in contrast to the initial xanthan, occurs in two stages. The DTG curve has two pronounced peaks, with maxima at 226 and 286 °C.